ANALISIS PENGARUH CURRENT RATIO, INVENTORY TURNOVER, DEBT TO EQUITY RATIO DAN SIZE TERHADAP RETURN ON ASSET (Studi pada Perusahaan Automotive and Allied Product yang Listed di Bursa Efek Indonesia Tahun 2004 - 2009) - Yudha, Donny Prawira (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2011)
In an era of tight competition, competitive advantage has been developed and involves the impor tance of the company's financial performance. It is therefore important to further deepen the study of corporate financial performance. ROA is one indicator to measure the financial perfor mance of companies and is a profitability ratio that is used to measure the effectiveness of the company in making a profit by exploiting the total assets owned.Companies are selected to become the object of this study are automotive companies and allied products listed on the Indonesia Stock Exchange (BEi) in the period of study (periode 2004 - 2009). From a population of 19 companies, gained as much as 17 perusahaanOtomotit and allied products that meet the criteria for the sample. Which Include Current Ratio, Inventory Turnover, DER, Size and ROA, financial padalaporan during the period of study (periode2004 2009).Coefficient of determination (Adjusted R2) of 0246 or 24. 6%, ROA haltersebutberartivariasi which can be explained by the variation of four independent variables, namely: cash ratio, inventory turnover, size, and DER, while the rest equal to 75,4% explained by cause other cause beyond the independent model. Variabel current ratio, inventory turnover, size, and the same DER secara bersama significant effect on ROA. This is evident from the F test statistic with a signifi cance value of 0.001. The influence of cash ratio, inventory turnover, DER, and size is shown partially on the ROA parameters of each melalui uji t statistics. Variable DER and size, a significant effect on ROA, while inventory turnover and current ratio does not affect the ROA.At the company's automotive and allied products, company size (size) in the conduct of internal control, financing decisions and investment decisions. For the creditors and investors to better understand the profitability of automotive companies and allied products that can help policy making investment decisions. Disampingitu also concerned at the debt policy (DER) have a sig nificant effect on profitability, and firm size significantly influence profitabiltas. Thus, this research will provide management functionality tor the automotive and allied products companies to pay more attention to debt policy in the conduct of internal control, decisionfinancing and investment decisions in order to develop its business.